A Cross-Sectional Study of the Association between Overnight Call and Irritable Bowel Syndrome in Medical Students. (2012) - Wells, Malcolm; Roth, Lee; McWilliam, Morgan; Thompson, Kim; Chande, Nilesh
Abstract : BACKGROUND: Shift work has been associated with irritable bowel syndrome (IBS), which includes gastrointestinal symptoms such as abdominal pain, constipation and diarrhea. Overnight call shifts also lead to a disruption of the endogenous circadian rhythm. HYPOTHESIS: Medical students who perform intermittent overnight call shifts will demonstrate a higher prevalence of IBS symptoms when compared with medical students who perform no overnight call shifts. METHODS: First- and second-year (preclinical) medical students have no overnight call requirements, whereas third- and fourth-year medical (clerkship) students do have overnight call requirements. All medical students at the Schulich School of Medicine and Dentistry (London, Ontario) were invited to complete an anonymous, web-based survey or an identical paper copy that included demographic data, the Rome III questionnaire and the IBS-Quality of Life measure (IBS-QOL). The prevalence of IBS symptoms and quality of life secondary to those symptoms were determined. RESULTS: Data were available for 247 medical students (110 pre-clinical students, 118 clerkship students and 19 excluded surveys). There was no significant difference in the presence of IBS between preclinical and clerkship students (21 of 110 [19.1%] versus 26 of 118 [22.0%]; P=0.58). The were no significant differences in mean (± SD) IBS-QOL score of those with IBS between preclinical (43.5±8.3) and clerkship students (45.7±13.8) (P=0.53). CONCLUSIONS: Participation in overnight call was not associated with the development of IBS or a lower quality of life secondary to IBS in medical students.